2009
DOI: 10.1200/jco.2008.18.9035
|View full text |Cite
|
Sign up to set email alerts
|

Short Delay in Initiation of Radiotherapy May Not Affect Outcome of Patients With Glioblastoma: A Secondary Analysis From the Radiation Therapy Oncology Group Database

Abstract: There is no evident reduction in survival by delaying initiation of RT within the relatively narrow constraint of 6 weeks. An unanticipated yet significantly superior outcome was identified for patients for whom RT was delayed beyond 4 weeks from surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
96
4
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 40 publications
9
96
4
3
Order By: Relevance
“…[3][4][5][6][7] As the extent of surgical resection is known to significantly impact patient prognosis [8][9][10] , whether "biopsy-only" GBM patients receive a significant survival benefit to CRT over radiotherapy (RT) alone is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] As the extent of surgical resection is known to significantly impact patient prognosis [8][9][10] , whether "biopsy-only" GBM patients receive a significant survival benefit to CRT over radiotherapy (RT) alone is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…An unanticipated yet significantly superior outcome was identified for patients for whom RT was delayed beyond 4 weeks from surgery [61].…”
Section: Timing Of Postsurgical Therapymentioning
confidence: 99%
“…These results were similar to those of burnet et al, who developed a mathematical model for analyzing the data of patients with glioblastoma and found that delayed RT led to a negative prognosis. 18 blumenthal et al retrospectively analyzed 2,855 patients from 1974 to 2003 9 and reported that the time from surgery to the start of RT should be a maximum of six weeks as per the Radiation Therapy Oncology Group protocol. In their analysis, the median survival time in a group with a delay of more than four weeks in the initiation of RT was 12.5 months compared with 9.2 months in a group with a delay of less than two weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of RT to treatment protocols in three randomized phase III trials demonstrated an approximate doubling of survival and has been the considered standard of care since the late 1970's. [6][7][8] The standard time for RT for most patients is between two and six weeks following surgery 6,[9][10][11][12] ; however, in certain resource-limited centers, it may be as long as…”
mentioning
confidence: 99%